Pemberian Pendidikan Kesehatan Mempengaruhi Tingkat Pengetahuan Tentang Kanker Payudara - Wiwin Renny Rahmawati; Tulus Tulus; Moh Ridwan; Khumairotul Ulya (Indonesian National Nurses Association (INNA) of Central Java, 2019)
Background : Breast cancer is a type of malignant cancer that attacks women. The highest prevalence in Indonesia that attacks adolescence, this shows that knowledge is still low in young women about the importance of preventing breast cancer.Purpose : This study aimed to determine the level of knowledge of young women before and after being given health education about breast cancer.Methods : This type of research is quantitative research with research design using Quasi-Experimental. The instrument used for knowledge is a questionnaire. The sampling technique in this study used total sampling with a sample size of 84. Processing data used the Wilcoxon statistical test.Result : This study shows that the level of knowledge before health education 47.62% of girls have sufficient level of knowledge and the level of knowledge after health education 72.62% knowledge of adolescent girls in good categories, from the results of Wilcoxon statistical tests of knowledge before and after health education obtained grades p value 0.000 (p <0.05).Conclusion : There is an influence of health education on the level of knowledge about breast cancer. Keywords : Breast cancer, knowledge, health education.